BaCu2Sn(S,Se)4: Earth-Abundant Chalcogenides for Thin-Film Photovoltaics - Shin, Donghyeop; Saparov, Bayrammurad; Zhu, Tong; Huhn, William P; Blum, Volker; Mitzi, David B (Chemistry of materials, 2016)
Chalcogenides such as CdTe, Cu(In,Ga)(S,Se)2 (CIGSSe), and Cu2ZnSn(S,Se)4 (CZTSSe) have enabled remarkable advances in thin-film photovoltaic performance, but concerns remain regarding (i) the toxicity (CdTe) and (ii) scarcity (CIGSSe/CdTe) of the constituent elements and (iii) the unavoidable antisite disordering that limits further efficiency improvement (CZTSSe). In this work, we show that a different materials class, the BaCu2SnSe x S4–x (BCTSSe) system, offers a prospective path to circumvent difficulties (i–iii) and to target new environmentally friendly and earth-abundant absorbers. Antisite disordering and associated band tailing are discouraged in BCTSSe due to the distinct coordination environment of the large Ba2+ cation. Indeed, an abrupt absorption edge and sharp associated photoluminescence emission demonstrate a reduced impact of band tailing in BCTSSe relative to CZTSSe. Our combined experimental and computational studies of BCTSSe reveal that the compositions 0 ≤ x ≤ 4 exhibit a tunable nearly direct or direct bandgap in the 1.6–2 eV range, spanning relevant values for single- or multiple-junction photovoltaic applications. For the first time, a prototype BaCu2SnS4-based thin-film solar cell has been successfully demonstrated, yielding a power conversion efficiency of 1.6% (0.42 cm2 total area). The systematic experimental and theoretical investigations, combined with proof-of-principle device results, suggest promise for BaCu2SnSe x S4–x as a thin-film solar cell absorber.